Post-refolding stability considerations for optimization of in-vitro refolding: L-asparaginase as a case study - Mihooliya, Kanti Nandan; Nitika, Nitika; Bhambure, Rahul; Rathore, Anurag S. S. (Biotechnology Journal, 2023)
BackgroundL-Asparaginase is an essential enzyme for the food and biopharmaceutical industry. The stability, however, of L-asparaginase is widely known to be an issue. Commercial manufacturing of any biopharmaceutical involves hold-ups during processing, and can result in product loss if stability is an issue, as is the case with L-asparaginase. This interplay of product intermediate stability and process design is the focus of this investigation. Methods and ResultsIn this study, we propose a strategy to simultaneously increase the refolding yield and stability of refolded L-asparaginase so as to improve overall process yield. Using one variable at a time (OVAT) experiments, urea (6 M), solubilized inclusion bodies (15 mg/ml), refolding method (step dilution), and pH (8.6) were identified as significant process parameters. A design of experiment (DOE)-based optimization was then performed for the refolding step. The net outcome was more than a three-fold increase in enzyme recovery (i.e., 4.90 IU/ml) compared to unoptimized conditions (i.e., 1.26 IU/ml). Further, the L-asparaginase process intermediate was found to be stable for more than a week at room temperature and 2-8 degrees C, while the unoptimized sample was stable at 2-8 degrees C but did not show any activity at room temperature after 72 h. ConclusionsThe current study elucidates how process intermediate stability needs to be given due consideration during process optimization, particularly for products such as L-asparaginase which are labile.
Keywords: design of experiment; L-asparaginase; refolding; stability